Antioxidant and biotransformation responses in Liza aurata under environmental mercury exposure: relationship with mercury accumulation and implications for public health - Guilherme, S. (2008)
This study was carried out in the Laranjo basin (Ria de Aveiro, Portugal), an area impacted by mercury discharges. Liza aurata oxidative stress and biotransformation responses were assessed in the liver and related to total mercury (Hgt) concentrations. A seasonal fish survey revealed a sporadic increase in total glutathione (GSHt) and elevated muscle Hgt levels, although Hg levels did not exceed the EU regulatory limit. As a complement study, fish were caged for three days both close to the bottom and on the water surface at three locations, and displayed higher Hgt levels accompanied by increased GSHt content and catalase activity as well as EROD activity inhibition. The bottom group displayed higher hepatic Hgt and GSHt contents compared with the surface group. Globally, both wild and caged fish revealed that the liver accumulates higher Hgt concentrations than muscle and, thus, better reflects environmental contamination levels. The absence of peroxidative damage in the liver can be attributed to effective detoxification and antioxidant defense.